Cadmium Removal Using Bio-Electrochemical Reactor with Packed Bed Rotating Cylindrical Cathode: A Kinetics Study - A. Kadhim, Zahraa; H. Abbar, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The kinetics of removing cadmium from aqueous solutions was studied using a bio-electrochemical reactor with a packed bed rotating cylindrical cathode. The effect of applied voltage, initial concentration of cadmium, cathode rotation speed, and pH on the reaction rate constant (k) was studied. The results showed that the cathodic deposition occurred under the control of mass transfer for all applied voltage values ​​used in this research. Accordingly, the relationship between logarithmic concentration gradient with time can be represented by a first-order kinetic rate equation. It was found that the rate constant (k) depends on the applied voltage, the initial cadmium concentration, the pH and the rotational speed of cathode. It was increased with increasing the applied voltage and its relationship with the applied voltage obeyed an exponential formula. The rate constant (k) was decreased with increasing the initial concentration of cadmium higher than 150ppm while at low concentrations it was increased. pH and rotational speed have different effects on the rate constant. Increasing the pH from 3 to 6 increases the rate constant while a slight decrease in the rate constant occurs at pH = 7. Increasing the rotation from 100 to 500 rpm increases the rate constant; however, the rate constant became approximately constant buoyed 300 rpm.